Pengaruh Teknik Teratai Terhadap Kemampuan Menulis Eksposisi Oleh Siswa Kelas X SMA Swasta Erlangga Pematangsiantar - Resmi Resmi; Rahmat Kartolo Silitonga; Fheti Wulandari Lubis (Departement of Mathematics Education, 2023)
Study this aim for knowing influence technique lotus to ability write exposition by student class X SMA Swasta Erlangga Pematangsiantar. Sample in study this is class X SMA Swasta Erlangga Pematangsiantar, totaling 20 students . Type study this is study experiment with design one group pretest posttest design . Based on results study and data analysis can concluded that ability write text exposition use technique lotus experience enhancement in the learning process . This thing could seen from result data pretest with results the average value of 55.60 while the Posttest data show that student 's average score of 74.05. There is influence use technique lotus to ability write text exposition student class X SMA Swasta Erlangga Pematangsiantar teachings shown with score t count > t table ( 0.688 > 0.444).